1974
DOI: 10.1210/jcem-38-4-701
|View full text |Cite
|
Sign up to set email alerts
|

ACTH-Induced Sodium Retention in Pregnancy. Role of Desoxycorticosterone and Corticosterone*†

Abstract: Continued administration of ACTH to normal gravidas results in marked sodium retention that is sustained, while aldosterone excretion declines below pretreatment levels. Since this is similar to results noted in nonpregnant subjects, where the cumulative sodium retention has been ascribed to increments in ACTH-dependent mineralocorticoids such as desoxycorticosterone (DOC) and corticosterone (B), a study was designed to evaluate effects of administered ACTH in pregnancy upon the urinary excretion of DOC and B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 10 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Plasma progesterone: The plasma levels of DOC, a potent mineralocorticosteroid, in near-term pregnant women (500-3,500 pg/ml) and their fetuses (1,500-6,000 pg/ml) (316-324) are 20-100 times those in men and nonpregnant women during the follicular phase of the cycle (25-50 pg/ml) (325). Furthermore, the plasma levels of DOC are not reduced in pregnant or midluteal phase nonpregnant women by the administration of dexamethasone (to inhibit ACTH), and DOC levels in plasma are not increased by the administration of ACTH to these women (317)(318)(319)(320)(321)(322)(323)327). Furthermore, the plasma levels of DOC are not reduced in pregnant or midluteal phase nonpregnant women by the administration of dexamethasone (to inhibit ACTH), and DOC levels in plasma are not increased by the administration of ACTH to these women (317)(318)(319)(320)(321)(322)(323)327).…”
Section: Extraadrenal 21-hydroxylation Of Plasma Progesterone Pregnementioning
confidence: 99%
“…Plasma progesterone: The plasma levels of DOC, a potent mineralocorticosteroid, in near-term pregnant women (500-3,500 pg/ml) and their fetuses (1,500-6,000 pg/ml) (316-324) are 20-100 times those in men and nonpregnant women during the follicular phase of the cycle (25-50 pg/ml) (325). Furthermore, the plasma levels of DOC are not reduced in pregnant or midluteal phase nonpregnant women by the administration of dexamethasone (to inhibit ACTH), and DOC levels in plasma are not increased by the administration of ACTH to these women (317)(318)(319)(320)(321)(322)(323)327). Furthermore, the plasma levels of DOC are not reduced in pregnant or midluteal phase nonpregnant women by the administration of dexamethasone (to inhibit ACTH), and DOC levels in plasma are not increased by the administration of ACTH to these women (317)(318)(319)(320)(321)(322)(323)327).…”
Section: Extraadrenal 21-hydroxylation Of Plasma Progesterone Pregnementioning
confidence: 99%
“…Importantly, it was also found that treatment of nearterm pregnant women with dexamethasone or ACTH did not lead to significant changes in plasma DOC concentrations (2,4,5,7,12). However in pregnant women near term, urinary 3a,21-dihydroxy-5,8-pregnan-20-one (tetrahydro-DOC) excretion was increased by ACTH-treatment (12). Nolten et al (7) concluded that these results could be explained as follows: ACTH-treatment of pregnant women was associated with an increase in plasma cortisol concentration.…”
Section: Introductionmentioning
confidence: 95%
“…Their view was based on the findings that the levels of DOC and DOC-sulfate in umbilical cord plasma were higher than those in maternal plasma (2,6,10,11) and that within 16-24 h after delivery, maternal plasma levels of DOC fell to levels found in nonpregnant women and men (2,6). Importantly, it was also found that treatment of nearterm pregnant women with dexamethasone or ACTH did not lead to significant changes in plasma DOC concentrations (2,4,5,7,12). However in pregnant women near term, urinary 3a,21-dihydroxy-5,8-pregnan-20-one (tetrahydro-DOC) excretion was increased by ACTH-treatment (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, Winkel et al (7,8) noted that in all of these situations there were parallel increases in Prog secretion by the adrenal cortex and ovary. However, DOC in pregnant women was not stimulated or suppressed by ACTH, angiotensin, or dexamethasone (3,5,22,(25)(26)(27). However, DOC in pregnant women was not stimulated or suppressed by ACTH, angiotensin, or dexamethasone (3,5,22,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 98%